1988
DOI: 10.1038/clpt.1988.167
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphone levels and pain control in patients with severe chronic pain

Abstract: To better understand the use of narcotic analgesics, the hydromorphone concentration was measured in serum samples from 43 patients with chronic severe pain who were receiving this drug. At the time of blood sampling, pain intensity, mood, and cognitive performance were assessed. There was large individual variation in the dose-drug level relationship. Seven patients with bone or soft tissue pain and drug levels of greater than or equal to 4 ng/ml had good pain control, whereas 10 did not. None of 15 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…The short duration of analgesia, measured as increase of PPT, corresponds to the findings of Coda et al (9) and the absent analgesic effects at the lower plasma concentrations agree with the results of Reidenberg et al (30). The larger variability of the effect of hydromorphone on PPT compared with the variability observed in the nonanalgesic effects may reflect the well known interindividual variability of analgesic effect of a standard dose of an opioid (6).…”
Section: Discussionsupporting
confidence: 79%
“…The short duration of analgesia, measured as increase of PPT, corresponds to the findings of Coda et al (9) and the absent analgesic effects at the lower plasma concentrations agree with the results of Reidenberg et al (30). The larger variability of the effect of hydromorphone on PPT compared with the variability observed in the nonanalgesic effects may reflect the well known interindividual variability of analgesic effect of a standard dose of an opioid (6).…”
Section: Discussionsupporting
confidence: 79%
“…The usual indications for parenteral hydromorphone are difficulty in swallowing, nausea and vomiting, and altered consciousness [53,112,113]. Persons with chronic severe pain from bone or soft tissue tumor appear to require serum hydromorphone levels 1 4 ng/ ml to achieve pain control [88]. Hydromorphone can relieve continuous dull pain more effectively than sharp intermittent pain, but with sufficient amounts it is possible to relieve even the severe pain associated with renal or biliary colic [60].…”
Section: Painmentioning
confidence: 98%
“…The use of alternative m-receptor agonists, such as hydromorphone, has been hampered by the required 4-hourly dosing frequency. However, sustained-release hydromorphone is now available [15,41,48,88].…”
Section: Painmentioning
confidence: 99%
“…One reason is lack of readily available measurements of opioid analgesics. For example, a research study done with hospitalized patients receiving opioids for chronic severe pain found that 60% of patients with bone or soft tissue pain had plasma opioid concentrations lower than the lowest concentration in patients having pain relief (Reidenberg et al, 1988). There are large person-to-person differences in the metabolic inactivation of 5-fluorouracil (FU) by dihydropyrimidine dehydrogenese, and a study (Gamelin et al, 2008) using blood-level monitoring to adjust dosing regimens throughout drug therapy was shown to improve therapy.…”
Section: Perspectives For the Futurementioning
confidence: 99%